On literary expression in A. Vienuolis’ legends - Stonys, Juozas (Literatūra, 1974)
Legend was an abiding interest of the prominent Lithuanian writer A. Vienuolis (1882-1957). The article deals with the poetics of hislegends. At the beginning of the paper the relation of the literary legend to the folk-legend, or one of the main principles of assimilation of folklore by a writer is defined as stylization. The literary legend represents a conventional poetical structure which assimilates certain forms of folklore in a peculiar way. The works analysed show distinctly the disposition of the legend to provide the phenomena and personages described with utmost intensive, rare, and contrasting properties. This can be named as superlativism and it determines to some extent the whole structure of the legend. The manifestation of this principle can be observed in various components of a legend, not only in fantastic personages. It can be traced even in the development of descriptions and in the psychological motivation of the plot. The supernatural, fantastic elements can also be explained as the manifestation of this important principle. Personification, i.e. endowing nature with human characteristics, prevails in the descriptions of nature over the objective representation of it. At the end of the article the poetics of A. Vienuolis’ early legends is regarded in connection with similar phenomena of the Lithuanian art and literature and they are treated as a peculiar parallel to the phenomena of neoromanticism in other European literatures.